Relationships among beef carcass quality and cutability indicators - Lawrence, T.E.; King, D.A.; Montgomery, T.H.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated beef carcass data (12th rib fat thickness, hot carcass weight, ribeye area, percentage of kidney-pelvic-heart fat, USDA yield grade, and USDA quality grade) from 60,625 A-maturity steer and heifer carcasses. Data were analyzed to evaluate changes in quality grade with increasing fat thickness, changes in cutability indicators across quality grades, and the association of hot carcass weight with ribeye area. Percentage of USDA Standard and Select carcasses decreased, while Low Choice and Premium Choice increased as fat thickness increased. Percentage of Low Choice remained steady for fat thickness of 0.56 - 0.60 in. and higher. Percentage of yield grade 4.0 or greater carcasses increased dramatically as fat thickness increased beyond 0.60 in. Fat thickness, hot carcass weight, percentage of kidney-pelvic-heart fat, and USDA yield grade increased, while ribeye area decreased as quality grades improved. The association between hot carcass weight and ribeye area differs from USDA requirements. Our recently collected data indicate that as hot carcass weight increases, ribeye area increases at a slower rate than indicated by USDA guidelines. Feeding cattle to a backfat thickness of 0.51-0.55 in. will maximize quality grade while minimizing discounts for yield grade 4.0 or higher.
Keywords: Beef; Carcass; Cutability indicators; Quality grade; Yield grade